MENGUCAPKAN SALAM KEPADA NON MUSLIM (Analisis Teksal-Qur’an Hadits, Asbabul Wurud dan Implikasi Hukum) - Ahmad Hanif Fahruddin (Akademika, 2019)
This research is aimed at knowing the Islamic law of greeting non-Muslims. This research is based on the questions of which texts of the Qur'an and the Hadith showing greetings to Muslims and non-Muslims, what views of Muslim scholars about saying greetings to Muslims and non-Muslims, and what the historicity, meaning and legal implications of hadith regarding the prohibition of greetings to non-Muslims. Through literature studies, it is found that in the Qur'an and the Hadith there are several texts showing about greetings to non-Muslims as in the QS. al-Furqon, 63; QS. an-Nisa', 86; and QS. an-Nur, 27; and in the Hadith of Bukhari number 6258 and number 6926 and the Hadith of Muslim number 2163. However, there are different views among Muslim scholars in understanding the texts of the Qur'an and the Hadith about the possibility of greeting non-Muslims. Firstly, some Muslim scholars who do not allow greetings to non-Muslims with the argument of the hadith narrated from Abu Hurairah ra. Secondly, some Muslim scholars among the Prophet's companions, Ibn Abbas allowed to say greetings to non-Muslims because seeing the context of the prohibition of saying greetings to non-Muslims is when non-Muslims fought against the Prophet and Muslims.